Toxoplasmic encephalitis relapse rates with pyrimethamine-based therapy: systematic review and meta-analysis. (2nd January 2017) - Connolly, Mark P.; Goodwin, Elizabeth; Schey, Carina; Zummo, Jacqueline
Abstract: Toxoplasmic encephalitis (TE) is caused by Toxoplasma gondii infection and can be a life-threatening disease in immunocompromised patients. This study evaluated the rate of relapse associated with pyrimethamine-based maintenance therapy (i.e. secondary prophylaxis) in patients with human immunodeficiency virus (HIV) or AIDs treated prior to and after the common use (i.e. 1996) of highly active antiretroviral therapy (HAART) (pre-HAART and post-HAART, respectively). PubMed, Google Scholar, and Cochrane databases were searched to 6 June 2016 using search terms: pyrimethamine, Daraprim, Fansidar, Metakelfin, Fansimef, 5-(4-chlorophenyl)-6-ethyl-2, 4-pyrimidinediamine, encephalitis, cerebral, toxoplasmosis, toxoplasmic, and gondii . Single-arm cohort, retrospective, and randomized studies were included. Twenty-six studies with 1, 596 patients were included in the analysis; twenty pre-HAART ( n = 1, 228) studies and six post-HAART ( n = 368) were performed. Pooled proportions test for pyrimethamine-based therapy from pre-HAART studies indicated a relapse rate of 19.2% and 18.9% from the fixed-effects and random-effects models, respectively. The relapse rate in the post-HAART studies was 11.1% (fixed and random effects). Continuous therapy was suggestive of lower incidence of relapse compared with intermittent therapy in the pre-HAART era (range, 18.7 to 17.3% vs. 20.9 to 25.6%, respectively). These findings indicate that the likelihood of relapse associated with pyrimethamine-based therepy in patients with HIV and TE decreased after the introduction of HAART to approximately 11%. The findings have important implications as relapse may affect a patient's disease severity and prognosis, increase utilization of health care resources, and result in additional health care expenditure.